Theravada: Exploring the Original Teachings and Historical Legacy - Ananda, Bhikkhu (Journal of Buddhist Studies (T.U.), 2025)
This article investigates Theravāda Buddhism as the most historically grounded school of Buddhist thought, emphasizing its preservation of the earliest recorded teachings of the Buddha. It argues that Theravāda upholds doctrinal purity through a rigorous commitment to the Four Noble Truths, the Noble Eightfold Path, the Three Characteristics (Tilakkhaṇa), Dependent Origination, and Insight Meditation (Vipassanā). Drawing upon both canonical and comparative sources, the article traces the doctrinal, institutional, and textual evolution of Theravāda from the First Buddhist Council to the present day. The findings illuminate Theravāda’s enduring relevance, particularly its unique claim to canonical authenticity and its impact on contemporary Buddhist practice.